2019
DOI: 10.1039/c9ee00141g
|View full text |Cite
|
Sign up to set email alerts
|

Solvating power series of electrolyte solvents for lithium batteries

Abstract: From dictating the redox potential of electrolyte solvents to shaping the stability of solid-electrolyte interfaces, solvation plays a critical role in the electrochemistry of electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(169 citation statements)
references
References 40 publications
5
146
0
Order By: Relevance
“…By testing Zn electrolytes with a rigorous protocol designed with the ultimate goal of a RZMB in mind, it is possible to establish correlations between electrochemical performance and fundamental electrolyte properties, potentially guiding future electrolyte development. Echoing the work by Amine and co-workers, [29,30] we examined the role of the electrolyte solvent in the kinetics of interfacial charge transfer reactions and the deposition of a passivating interphase on the electrode surface. In the case of lithiumion batteries or batteries with Li metal anodes, it has been argued that the solvating strength of the electrolyte solvents should be lessened to promote salt aggregation, so that preferential reduction of fluorinated anions can outcompete solvent reduction, leading to an inorganic and dense solid electrolyte interphase (SEI).…”
Section: Resultsmentioning
confidence: 99%
“…By testing Zn electrolytes with a rigorous protocol designed with the ultimate goal of a RZMB in mind, it is possible to establish correlations between electrochemical performance and fundamental electrolyte properties, potentially guiding future electrolyte development. Echoing the work by Amine and co-workers, [29,30] we examined the role of the electrolyte solvent in the kinetics of interfacial charge transfer reactions and the deposition of a passivating interphase on the electrode surface. In the case of lithiumion batteries or batteries with Li metal anodes, it has been argued that the solvating strength of the electrolyte solvents should be lessened to promote salt aggregation, so that preferential reduction of fluorinated anions can outcompete solvent reduction, leading to an inorganic and dense solid electrolyte interphase (SEI).…”
Section: Resultsmentioning
confidence: 99%
“…[161] Copyright 2017, Royal Society of Chemistry; Copyright 2019, Royal Society of Chemistry. [162] www.afm-journal.de www.advancedsciencenews.com…”
Section: Summary and Perspectivementioning
confidence: 99%
“…further found that the solvating power of individual organic solvents critically determining the electrochemical performance of LIBs. [ 162 ] Using a newly developed internally referenced diffusion‐ordered spectroscopy technique and diffusion coefficient‐coordination ratio ( D –α) analysis, they have identified the solvating power of most organic solvents (Figure 34c). As a result, by using a combination of low solvating power (FEMC and FEC), the NCM622/Li cell demonstrated much better cycle performance (Figure 34d) and coulombic efficiency (Figure 34e) than GENII electrolyte (EC and EMC).…”
Section: Strategies To Advance Ni‐rich Layered Cathodes Under Harsh Omentioning
confidence: 99%
See 1 more Smart Citation
“…Yet how the electrolyte species interact with the Li metal electrode under electrochemical conditions and affect the performance of Li metal batteries (LMBs) are not well understood. Solvation of the Li + ion is considered to be important to the chemistry at the electrode/electrolyte interface . Various techniques, including vibrational spectroscopy (FTIR or Raman), electrospray ionization mass spectrometry, and nuclear magnetic resonance spectroscopy have been employed to study the structure of the solvation sheath and to understand the interfacial chemistry on the molecular level.…”
Section: Figurementioning
confidence: 99%